Using Mediation Method in Customary Justice of Aceh-Indonesia - MH, Nurdin; Dahlan, Dahlan; Suhaimi, Suhaimi; Mustakim, Mustakim (International Asia Of Law and Money Laundering, 2024)
Mediation is an Alternative Dispute Resolution regulated in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Mediation is divided into two types: mediation in and outside court. Private mediators, both individuals and institutions, handle out-of-court mediation. Meanwhile, mediation in court is regulated by Supreme Court Regulation No. 1 of 2016, which requires mediation before examining the main case, which is handled by judges or non-judge mediators recognized by the state. In Aceh Province, kampong (village) or mukim (collection of several villages) institutions carry out out-of-court mediation through a forum called the Aceh Customary Court. The Acehnese Customary Court has been around for hundreds of years. It continues to exist because it can administer justice cheaply and quickly, with simple procedures, easily accessible resolution forums (customary justice forums) found in the village itself, and able to realize a sense of justice that has been abolished in culture. The local community's law (legal culture) refers to the legal norms that live in society (living law). The Village Head acts as a mediator to encourage the parties to reach a mutual agreement that is a win-win solution to their situation. The legal basis for administering the Acehnese Customary Court is regulated in Aceh Qanun No. 9 of 2008 concerning the Development of Customs and Customs, Aceh Qanun No. 10 of 2008 concerning Traditional Institutions, and Aceh Qanun No. 8 of 2019 Council on Acehnese Customs. The research results show that implementing Acehnese customary justice uses a mediation method, where the peace agreement is made by the parties themselves, facilitated by mediators, in this case, traditional leaders (customary justice providers).